Toward a Methodology for Analyzing Visual Rhetoric in Corporate Reports. (July 2019) - Greenwood, Michelle; Jack, Gavin; Haylock, Brad
This article presents a methodology that organizational scholars can use to analyze, explain, and critically interpret the role of visual rhetoric in organizational communications. Corporations invest heavily in the visual design of organizational communications, including corporate reports, recognizing the distinctive role and benefits of visual imagery, as well as the rhetorical function of these documents. Current analytical approaches to visual rhetoric are either predominantly theoretical (with little structured guidance) or procedural (with little acknowledgment of important epistemic questions). This leaves a need for a methodology that combines a clear theoretical framework with explicit guidance on how to analyze visual rhetoric. This article bridges this analytic gap by offering a methodology that integrates a theoretical foundation of a priori analytical categories informed by selected writings of the French cultural theorist Roland Barthes with three abductively derived phases (categorical analysis, content analysis, rhetorical analysis) for analysis of visual design of corporate reports. We apply this methodology in an examination of a Qantas Annual Review and articulate our contributions to the field of organizational research methods.